Game Analysis on Rural Land Transfer from the Perspective of Stakeholder Theory - Gen Zhang; Qiance Zhang (SHS Web of Conferences, 2014)
The key—to maintaining social stability in rural areas, promoting rural economic development and building a new socialist countryside—is handling correctly the issues of rural land transfer and ironing out the conflicts resulting from the benefits imbalance. In this paper, rural land transfer is categorized into two types: land transfer caused by the collective behavior and land transfer caused by the individual behavior. In the process of land transfer caused by the collective behavior, the conflicts root in the convergence of interest among various rural social strata; while in the process of land transfer caused by the individual behavior, the game between interests and human relationship, reflects the dilemma between rationality and sensibility, which villagers are confronted with.